2009
DOI: 10.1590/s0102-76382009000200005
|View full text |Cite
|
Sign up to set email alerts
|

Resultados da implementação de modelo organizacional de um serviço de cirurgia cardiovascular

Abstract: Resultados da implementação de modelo organizacional de um serviço de cirurgia cardiovascularResults of the establishment of an organizational model in a cardiovascular surgery service Abstract Objective: Increasing complexity of patients referred to cardiac surgery demands more effective heart centers, in order to maintain the same quality. The aim of this study is to examine the short-term effect of adoption of an organizational model on surgical outcomes.Methods: From January 2006 to June 2007, 367 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
5
0
3
Order By: Relevance
“…Multimodal protocols belong to the reality of CVS, also being recommended in guideline for CABG [2][3][4][5][6]26]. De Vries et al [6] compared 3760 patients who underwent CVS before implementation of a protocol checklist, with 3820 patients operated after implementation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multimodal protocols belong to the reality of CVS, also being recommended in guideline for CABG [2][3][4][5][6]26]. De Vries et al [6] compared 3760 patients who underwent CVS before implementation of a protocol checklist, with 3820 patients operated after implementation.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of patients with complications decreased from 15.4% to 10.6% (P<0.001). In Brazil, reference centers in CVS have been concerned with the creation and deployment of multimodal protocols, with the proposition of risk scores for patients undergoing CABG and maintaining databases in order to assess the results and adoption of impact measures for improvements [2][3][4][5][31][32][33][34]. Atik et al [5] showed that after adoption of the organizational model, there was a reduction in hospital mortality (from 12% to 3.6%, RR=0.3, P=0.003), as well as adverse events combined (22% to 15%, RR=0.68, P=0.011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mobilizados diante de situação estressante como, medo, dúvida e alterações emocionais (14,15) . (16) . No caso de crianças o uso do brinquedo mostrou-se uma forma adequada para comunicar-se efetivamente com a criança .…”
Section: Comunicação E Relacionamento Terapêutico Pré-operatóriounclassified
“…O desenvolvimento tecnológico na área de Medicina tem permitido que operações cardiovasculares fossem conduzidas com segurança e resultados melhores. Fatores institucionais e pessoais estão envolvidos nesses bons resultados para melhor atendimento na assistência pós-operatória, exigindo dos profissionais atitudes, conhecimentos e habilidades específicas 11,12 .…”
Section: Introductionunclassified